2015
DOI: 10.1038/cdd.2014.221
|View full text |Cite
|
Sign up to set email alerts
|

Reactivation of epigenetically silenced miR-512 and miR-373 sensitizes lung cancer cells to cisplatin and restricts tumor growth

Abstract: MicroRNAs (miRs) regulate a variety of cellular processes, and their impaired expression is involved in cancer. Silencing of tumorsuppressive miRs in cancer can occur through epigenetic modifications, including DNA methylation and histone deacetylation. We performed comparative miR profiling on cultured lung cancer cells before and after treatment with 5′aza-deoxycytidine plus Trichostatin A to reverse DNA methylation and histone deacetylation, respectively. Several tens of miRs were strongly induced by such '… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 53 publications
2
48
1
3
Order By: Relevance
“…The association of a series of miRNAs with cellular apoptosis has been previously experimentally verified (25)(26)(27). In the present study, it was demonstrated that miR-1915-3p was a candidate regulator of lung cancer cell apoptosis.…”
Section: A B Discussionsupporting
confidence: 64%
“…The association of a series of miRNAs with cellular apoptosis has been previously experimentally verified (25)(26)(27). In the present study, it was demonstrated that miR-1915-3p was a candidate regulator of lung cancer cell apoptosis.…”
Section: A B Discussionsupporting
confidence: 64%
“…There have also been multiple reports on the role of miR‐486 in tumorigenesis, some concluding that it acts as a tumor suppressor of LUSC . miR‐515 has also been reported as a tumor suppressor, and similarly, studies have shown that miR‐512 not only inhibits glycolysis but also accelerates apoptosis . So far, there are few reports of a role for miR‐516 or miR‐525 in LUSC, however, there is evidence that they can regulate target genes in other tumors to affect protein expression .…”
Section: Discussionmentioning
confidence: 99%
“…[38][39][40] miR-515 has also been reported as a tumor suppressor, 41,42 and similarly, studies have shown that miR-512 not only inhibits glycolysis but also accelerates apoptosis. 43,44 So far, there are few reports of a role for miR-516 or miR-525 in LUSC, however, there is evidence that they can regulate target genes in other tumors to affect protein expression. 45,46 miR-577 affects cell expression by regulating the Wnt signaling pathway, which subsequently affects cell growth and cell viability.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some studies indicate that micro RNA (miRNA) analysis of exosomes might be useful for the diagnosis of lung adenocarcinoma (6971) and that particular miRNAs can offer prognostic information in advanced NSCLC. For example, downregulation of miRNA-373 and miRNA-512 has been associated with a poor prognosis (72), miR-208a and miR-1246 with resistance to radiotherapy (73, 74), and miR-221-3p and 222-3p with good response to osimertinib in EGFR mutated patients (75). …”
Section: Exosomesmentioning
confidence: 99%